2021
DOI: 10.2196/30854
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Public Opinion Towards COVID-19 Vaccines With Twitter Data in the United States: Spatiotemporal Perspective

Abstract: Background The COVID-19 pandemic has imposed a large, initially uncontrollable, public health crisis both in the United States and across the world, with experts looking to vaccines as the ultimate mechanism of defense. The development and deployment of COVID-19 vaccines have been rapidly advancing via global efforts. Hence, it is crucial for governments, public health officials, and policy makers to understand public attitudes and opinions towards vaccines, such that effective interventions and ed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(94 citation statements)
references
References 51 publications
4
89
0
1
Order By: Relevance
“…The provision of mental health services and the implementation of mental health policies need to adjust at different phases of the pandemic. Digital health platforms and diverse channels (eg, text messaging, mobile health applications, telehealth and telemedicine) to deliver mental health services need to be incorporated to guide through the public’s mental status 7. The key contribution of our study is for the delineation of when and where people are displaying higher levels of pessimistic mental health signals provides important information through which the allocation of finite mental health facilities and services can be deployed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The provision of mental health services and the implementation of mental health policies need to adjust at different phases of the pandemic. Digital health platforms and diverse channels (eg, text messaging, mobile health applications, telehealth and telemedicine) to deliver mental health services need to be incorporated to guide through the public’s mental status 7. The key contribution of our study is for the delineation of when and where people are displaying higher levels of pessimistic mental health signals provides important information through which the allocation of finite mental health facilities and services can be deployed.…”
Section: Discussionmentioning
confidence: 99%
“…The public’s negative sentiment (eg, depression, fear, sadness and anxiety) toward COVID-19 has been observed in studies in the USA,2 UK,3 Australia4 and China,5 alongside a number of European nations 6. Furthermore, the elevated need for mental health services has been reported, although the increasing prevalence of vaccination may act to lower the negativity toward COVID-19 7. As the United Nations’ policy brief COVID-19 and the need for action on mental health,8 it concluded that an increased level of mental health crises in the era of COVID-19 is a priority worth a prompt response urgently planned by each country.…”
Section: Introductionmentioning
confidence: 99%
“…The big data method has created new stimulation for the research of public sentiment ( 7 10 ). Hu et al ( 11 ) accrued over 300,000 geotagged tweets in the United States from March 1, 2020 to February 28, 2021 and examined the spatiotemporal patterns of public sentiment and emotion over time at the national and state levels. The researchers discovered that in most states, an increasing trend in positive sentiment was observed in conjunction with a decrease in negative sentiment, reflecting the public's rising confidence and anticipation toward vaccines.…”
Section: Application Of the Big Data Methodsmentioning
confidence: 99%
“…Recently, topic modeling on data collected via social network services (SNSs), such as Twitter, and web portals is widely used for the survey of public perceptions and attitudes toward the COVID-19 outbreak [ 6 , 7 ], containment strategies [ 8 , 9 ], treatment interventions [ 6 ], and vaccines [ 10 , 11 ]. Topic modeling on SNS data is useful for examining issues that change quickly over time [ 12 ].…”
Section: Introductionmentioning
confidence: 99%